Whole-genome sequencing of Alcaligenes sp. strain MMA: insight into the antibiotic and heavy metal resistant genes - Sodhi, Kushneet Kaur; Singh, Chandra Kant; Kumar, Mohit; Singh, Dileep Kumar (Frontiers in Pharmacology, 2023)
A wide range of pollutants including the likes of xenobiotics, heavy metals, and antibiotics are the characteristic of marine ecosystems. Increased use and misuse of antibiotics in the medicine, agriculture and veterinary has posed a grave concern over antimicrobial resistance. The exposure of these heavy metals and antibiotics in the bacteria drives the evolution of antibiotic and heavy metal resistant genes. In the earlier study by the author Alcaligenes sp. MMA was involved in the removal of heavy metals and antibiotics. Alcaligenes display diverse bioremediation capabilities but remain unexplored at the level of genome. To shed the light on its genome, the Alcaligenessp. strain MMA, was sequenced using Illumina Nova Seq sequencer which resulted in a draft genome of 3.9 Mb. The genome annotation was done using Rapid annotation using subsystem technology (RAST) revealed the presence of 3685 protein-coding genes. Given, the spread of antimicrobial resistance, and the generation of multi-drug resistant pathogens (MDR), the strain MMA was checked for the potential antibiotic and heavy metal resistance genes. Multiple metal resistant genes and genes conferring resistance to tetracycline, beta-lactams, and fluoroquinolones were present in the draft genome. Further, we checked for the presence of biosynthetic gene clusters in the draft genome and many types of BGCs were predicted such as siderophore. The secondary metabolites of fungi and bacteria are a rich source of novel bioactive compounds which have a potential as in new drug candidates The results of this study provide information on the strain MMA genome and are valuable for the researcher in further exploitation of the strain MMA for bioremediation. Moreover, the whole-genome sequencing has become a useful tool to monitor the spread of antibiotic resistance, a global threat to healthcare.